Probiotic therapy in couples with infertility: A systematic review. (January 2021) - Corbett, GA; Crosby, DA; McAuliffe, FM
Abstract: The reproductive microbiome is becoming increasingly recognised for its influence on fertility. While there has been much work to investigate the treatment of bacterial vaginosis and disordered microbiomes in optimizing outcomes in Assisted Reproductive Technology (ART), the role of routinely prescribed probiotics is yet to be established. The therapeutic potential of probiotic therapy remains an exciting opportunity in ART and this review endeavours to summarise its evidence to date. A systematic review of MEDLINE (Pubmed), Allied Health Literature (CINAHL), EMBASE, Web of Science and the Cochrane database was performed on 7th May 2019, and repeated on 26th August 2019. The search was built using the terms 'subfertility;' 'probiotic therapy;' 'clinical pregnancy rate' and 'assisted reproductive outcomes.' The primary outcome was change in clinical pregnancy rate. Secondary outcomes included improvements in male and female fertility parameters and microbial assessment. The initial search found 882 articles, of which 26 full manuscripts were reviewed. Four articles were eligible for inclusion. Of the two studies that reported the primary outcome, only one study found probiotics increased the clinical pregnancy rate non-significantly (48.0%–58.8%, p = 0.47). It also found higher miscarriage rate (30 % vs 16.6 %, p = 0.47) in the group treated with probiotics. Both studies on males with oral probiotic found significantly improved sperm motility. While benefit in sperm motility has been observed with male probiotic therapy, there is conflicting evidence on the efficacy of probiotic therapy for women undergoing assisted reproduction. High quality randomized studies are needed to definitively examine probiotic therapy and establish its benefit for couples undergoing assisted reproduction.